Population Structure, Morphology, and Health Assessment of Philippine Swamp Buffalo (Bubalus kerabau, Fitzinger, 1860) in Calayan Island, Cagayan - Lilian P. Villamor; Aivhie Jhoy E. Cuanang; Therese Patricka C. Cailipan; Alexander M. Paraguas; Ester B. Flores; Marvin A. Villanueva; Michelle M. Balbin; Lawrence P. Belotindos; Franklin T. Rellin (Ruminants)
Understanding the state of the swamp buffalo population in Calayan Island is important to strengthen the conservation and management program in the country. This study aimed to provide insights into the morphology, population structure, and health profile of the swamp buffaloes on the island. In total, 35 fresh blood samples were analyzed using 27 polymorphic microsatellite markers to determine the population structure analysis. Data were gathered for the morphological features of Calayan swamp buffaloes and served as the baseline information for the descriptive traits. Furthermore, samples were tested for surra and brucellosis using PCR and serological tests, respectively. The results showed that Calayan swamp buffaloes were morphologically bigger, except for body length, compared with other populations. A genotype analysis using microsatellite markers showed remarkable discriminatory power to distinguish distinct populations within the tested population, and could discriminate subspecies of swamp and river types plus crossbreds. The study also reports the first incidence of surra and brucellosis on the island. Overall, the new insights provided on the newly detected Philippine carabao lineage in Calayan Island would be highly recommended for the ex situ conservation and animal health control strategy. The conservation strategy would encompass collecting, cryopreserving, and storing viable germplasms from local swamp buffalo on Calayan Island.